On defining and measuring the informal sector - Andrew Henley; G. Reza Arabsheibani; Francisco G. Carneiro (Institute for the Study of Labor (IZA), 2006)
A range of alternative empirical definitions of informal activity have been employed in the literature. Choice of definition is often dictated by data availability. Different definitions may imply very different conceptual understandings of informality. This paper investigates the degree of congruence between three definitions of informality based on employment contract registration, on social security protection and the characteristics of the employer and employment using Brazilian household survey data for the period 1992 to 2001. 64% of the economically active are informal according to at least one definition, but only 40% are informal according to all three. Steady compositional changes have been taking place amongst informal workers, conditional on definition. Econometric analysis reveals that the conditional impact of particular factors (demographic, educational attainment, family circumstances) on the likelihood of informality varies considerably from one definition to another. Results suggest growing heterogeneity within the informal sector. Informal activity may be as much associated with entrepreneurial dynamism as with any desire to avoid costly contract registration and social protection. However there is no a priori reason for entrepreneurial activity to be unprotected. Results in the paper confirm this. Consequently definitions of informality based on occupation and employer size seem the most arbitrary in practice even if conceptually well-founded.
urn:nbn:de:101:1-2008051661
Keywords: 330; Informeller Sektor; Arbeitsmarkt; Brasilien